Enhancement of Quality Parameters of Chicken Meat Momos by Incorporation of Minced Fish Meat Incorporation of Minced Fish Meat - Tanuja,; V, Pathak,; A. K, Verma,; V., Rajkumar,; M. , Goswami,; V. P, Singh, (Journal of Meat Science, 2019)
The present study was carried out to enhance the nutrition and other quality parameters of chicken meat momos with the incorporation of minced fish meat. A total of five treatments consisting of 100% chicken meat as control (C), 25% of fish meat (F1), 50% of fish meat (F2), 75% of fish meat (F3) and 100% fish meat (F4) were prepared and evaluated for various physico-chemical properties, color and textural profile analysis as well as sensory attributes. There was no significant difference in mean pH value, cooking yield, weight gain and water activity but significant difference (P
Keywords: Chicken momos; minced fish meat; nutrition; quality parameters